Tailoring graphene-supported Ru nanoparticles by functionalization with pyrene-tagged N-heterocyclic carbenes. Issue 4 (14th January 2022) - García-Zaragoza, Adrián; Cerezo-Navarrete, Christian; Mollar-Cuni, Andrés; Oña-Burgos, Pascual; Mata, Jose A.; Corma, Avelino; Martínez-Prieto, Luis M.
Abstract : Controlling the reactivity and stability of graphene-supported Ru NPs by modifying their surface with pyrene-tagged N -heterocyclic carbene ligands. Abstract : The catalytic properties of graphene-supported ruthenium nanoparticles (Ru@rGO) have been finely tuned by modifying their metal surface with pyrene-tagged N -heterocyclic-carbene ligands (pyr-IMes). The nature and interaction modes of the pyr-IMes ligands on Ru@rGO were established by XPS, which were found as protonated carbenes, coordinated to the ruthenium surface and directly interacting with the graphene support. To evaluate the activity and selectivity of Ru@rGO functionalized with different equivalents of pyr-IMes (Ru@rGO/pyr-IMes n ; n = 0, 0.2, 0.5, 0.8 or 1), we used acetophenone hydrogenation as a model reaction. The catalytic activity and selectivity are highly dependent on the NHC surface coverage degree. The higher the amount of surface NHC ligands, the lower the activity of the catalyst, but the higher the selectivity towards 1-phenylethanol (suppressing the hydrodeoxygenation side reaction at high surface coverages). The reactivity of the most interesting catalyst, Ru@rGO/pyr-IMes0.5, was evaluated in the hydrogenation of other molecules of interest, such as nitrobenzene, 5-hydroxymethylfurfural (HMF), quinoline or 1-methylindole, among others. Finally, by TEM analysis after catalysis we observed a clear correlation between the surface ligand coverage and the stability of the catalysts against sintering. It was then possible to control the reactivity and stability of graphene-supported Ru NPs by modifying their surface with pyr-IMes ligands.